Unveiling the Original Polychromy of Archaic Architecture: The Gigantomachy on the West Pediment of the Temple of Apollo at Delphi (6th c. B.C.) - Giasemi G. Frantzi; Georgios P. Mastrotheodoros; Panayiotis Theoulakis; Sotiria Kogou; Athanasia Psalti; Hariclia Brecoulaki (Heritage)
The Gigantomachy depicted on the west pediment of the Late Archaic temple of Apollo at Delphi marks a significant milestone in early Greek architectural sculpture. Crafted from porous stone and enhanced with plaster and paint, the surviving fragments differ markedly from the marble figures of the east pediment of the same temple. Among the preserved figures of the Gigantomachy are a standing male figure, possibly representing Apollo or Dionysos, a warrior female identified as Athena, and a recumbent male, likely symbolizing the Giant Enkelados. This study aims to investigate the polychromy of the west pediment through a thorough investigation of the remnants of the original decoration. The adopted methodology includes exclusively non-destructive techniques and advanced imaging methods, such as portable X-ray fluorescence spectrometry, visible-induced luminescence (VIL), and 3D microscope observation. Analytical results confirmed the presence of extensive traces of once-vibrant colors on the plaster’s surface, which were often invisible to the naked eye. Specifically, our data support the employment of pigments like Egyptian blue, cinnabar, ochre-based reds and yellows, as well as copper-based green. Notably, these pigments were applied over a white calcium-rich layer, which served as a primer for the porous stone. Ongoing research on the Gigantomachy promises to deepen our understanding of color usage and painting techniques in Archaic Greek art.